Does E-Learning Content Design Affect Student Learning Outcomes? - Nisail Mugni Hidayati (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2020)
This study aims to determine and analyze the effect of e-learning content design in the economic subject on learning outcomes moderated by student gender. The level of content design is measured through indicators of interface design, functionality, system support, usability, convenience, satisfaction, goals, active learning style, basic concepts, problem solving and experience. The level of learning outcomes is measured through the indicator of the test score results. This study uses an explanatory survey method with data collection techniques through questionnaires those are distributed to 197 students of the Social Sciences major with a sample of 132 students at SMA Negeri 1 Rengasdengklok. The data analysis technique uses descriptive statistics, inferential statistics and regression analysis. The results of this study indicate 1) The level of content design has a positive effect on the level of learning outcomes. The higher the level of e-learning content design on the economic subject, the higher the learning outcomes will be obtained by students. 2) Gender does not moderate the positive effect of the level of content design on the level of learning outcomes. However, the positive influence on content design for the male group is stronger.